The interactive role of income (material position) and income rank (psychosocial position) in psychological distress: a 9-year longitudinal study of 30,000 UK parents - Garratt, E; Chandola, T; Purdam, K; Wood, A (Springer Berlin Heidelberg, 2016)
Parents face an increased risk of psychological distress compared with adults without children, and families with children also have lower average household incomes. Past research suggests that absolute income (material position) and income status (psychosocial position) influence psychological distress, but their combined effects on changes in psychological distress have not been examined. Whether absolute income interacts with income status to influence psychological distress are also key questions.We used fixed-effects panel models to examine longitudinal associations between psychological distress (measured on the Kessler scale) and absolute income, distance from the regional mean income, and regional income rank (a proxy for status) using data from 29,107 parents included in the UK Millennium Cohort Study (2003-2012).Psychological distress was determined by an interaction between absolute income and income rank: higher absolute income was associated with lower psychological distress across the income spectrum, while the benefits of higher income rank were evident only in the highest income parents. Parents' psychological distress was, therefore, determined by a combination of income-related material and psychosocial factors.Both material and psychosocial factors contribute to well-being. Higher absolute incomes were associated with lower psychological distress across the income spectrum, demonstrating the importance of material factors. Conversely, income status was associated with psychological distress only at higher absolute incomes, suggesting that psychosocial factors are more relevant to distress in more advantaged, higher income parents. Clinical interventions could, therefore, consider both the material and psychosocial impacts of income on psychological distress.